Mechanism of inhibition of LTP induction by preconditioning stimulation in the rat dentate gyrus in vitro - Gisabella, Barbara (Trinity College (Dublin, Ireland). Department of Physiology, 2003)
The modulation of synaptic plasticity (LTP) by prior synaptic activity represented by preconditioning stimulation (weak HFS) was investigated in the medial perforant pathway of the dentate gyrus in vitro. The inhibition of LTP by preconditioning stimulation represented by weak HFS has been observed previously in CA1 (Huang et al, 1992). The results reported in this thesis have verified that similar inhibition occurs in the medial perforant path of the dentate gyrus. In addition, a possible model for the mechanism of inhibition of LTP by preconditioning stimulation has been proposed. Previous synaptic activity resulting in a change in the capabilities of synapse to undergo subsequent plasticity has been referred to as metaplasticity.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin